An Analysis of Teacher Speech Act in Giving Motivation for English Students - Muhammad Azizul Chakim; Haris Dibdyaningsih (STKIP AL HIKMAH SURABAYA, 2019)
Speaking is defined as a reflection of the students’ ability to communicate in English. Compared to the other language skills, speaking is considered to be more difficult because it occurs in real time, and when we speak we cannot edit and revise what we want to say, as we can do in writing. Speaking skill was considered as a difficult skill to be maintained; therefore, an extensive practice is required to perform. However, students tend to be silent in the classroom since they lack of self-confidence. Students need more practice, so that they could learn to express their feeling, thought, idea, emotion and intention, whereas, teachers should create a good situation in teaching learning process in the classroom. Gallery walk is one of the most learner centered activities which provides good situation in teaching learning process. It is a presentation method in which individual learners or groups displayed their products, and they walked around the room viewing others’ work. The purpose of this paper is to describe gallery walk technique to teach speaking in Senior High School. This technique seems to be suitable to provide fresh atmosphere in teaching English especially in Speaking.